Global burden, regional disparities, and future projections of hypertensive kidney disease in older adults: analysis of GBD 1990–2021 data - Li, Juan; Jiao, Zeyu; Cheng, Fang; Liu, Ting; Kang, Ruixia; Cai, Yongyuan; Zhang, Ruifang; Xue, Xiaoming (Frontiers in Nephrology, 2025)
AimsHypertensive kidney disease (HKD) contributes significantly to global morbidity and mortality. This study evaluated the burden of HKD in older adults (≥60 years) across 204 countries from 1990 to 2021 and projected trends to 2045.MethodsData from the Global Burden of Disease Study 2021 were used to estimate HKD prevalence, incidence, mortality, and disability-adjusted life years (DALYs). Age-standardized rates (ASRs) were calculated with 95% uncertainty intervals (UIs). Temporal trends were analyzed using Joinpoint regression. Slope and concentration indices quantified health inequality. Decomposition and frontier analyses explored burden drivers. Future projections were made using Nordpred-based Bayesian age-period-cohort models. Sensitivity analyses assessed model robustness. Risk-attributable mortality was also estimated.ResultsIn 2021, global ASRs were 1674.9 (prevalence), 93.4 (incidence), 36.5 (mortality), and 631.1 (DALYs) per 100,000 older adults. High-SDI regions had higher prevalence (ASPR: 1857.8) and incidence (ASIR: 126.5), while low-SDI regions showed higher mortality (ASMR: 58.6) and DALY rates (ASDR: 972.7). Males across all age groups had higher prevalence (e.g. 95 plus: 9109.6 vs. 7031.5 per 100,000). Leading risk factors included low fruit intake (6.98 deaths per 100,000), high sodium, and lead exposure. From 1990-2021, ASIR (AAPC = 0.63%), ASMR (0.99%), and ASDR (0.77%) rose, while ASPR declined (-0.25%). Decomposition attributed burden increases mainly to population growth (72.3%) and aging (6.7%). Frontier analysis revealed substantial room for improvement in middle-SDI countries. Sensitivity analyses confirmed the stability of trend estimates and projections. Forecasts indicate that deaths in adults ≥90 will triple by 2045 (e.g. 95 plus: 75,271 vs. 20,242 in 2021).ConclusionHKD burden has grown substantially, with persistent geographic and socioeconomic disparities. Effective mitigation requires not only demographic- and region-specific interventions but also improved access to early detection and dietary risk reduction. Integration of kidney care into primary health systems and aging-focused strategies will be crucial to curb future disease escalation.